2020
DOI: 10.1177/1542305020948189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spiritual Care on Chest Tube Removal Anxiety and Pain in Heart Surgery in Muslim Patients (Shia and Sunni)

Abstract: The process of removal of a chest tube can cause pain and anxiety. Spiritual care can be considered as a component of nursing care, especially in the pain and anxiety relating to such procedures. This study was a randomized clinical trial. Eighty patients completed the study. The findings showed significant differences in anxiety and pain between groups ( p = 0.001). Spiritual care reduced anxiety and pain caused by chest tube removal in patients (Shia and Sunni Islam) undergoing heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In line with the results of the study, examining the effect of spiritual care on patients with general anxiety and depression, a randomized controlled study showed that there was a significant improvement in anxiety and depression symptoms in the spiritual care group compared to the control group (Sankhe et al, 2017). The results of other studies showed that providing spiritual care for other diseases and interventions, it is associated with a reduction in anxiety in patients and their families (Borji et al, 2019;Fasihizadeh & Nasiriani, 2020;Hosseini et al, 2014) (Ravari et al, 2017) (Borji et al, 2019) (Tajbakhsh et al, 2016). These studies confirm the results of the present study.…”
Section: Discussionsupporting
confidence: 64%
“…In line with the results of the study, examining the effect of spiritual care on patients with general anxiety and depression, a randomized controlled study showed that there was a significant improvement in anxiety and depression symptoms in the spiritual care group compared to the control group (Sankhe et al, 2017). The results of other studies showed that providing spiritual care for other diseases and interventions, it is associated with a reduction in anxiety in patients and their families (Borji et al, 2019;Fasihizadeh & Nasiriani, 2020;Hosseini et al, 2014) (Ravari et al, 2017) (Borji et al, 2019) (Tajbakhsh et al, 2016). These studies confirm the results of the present study.…”
Section: Discussionsupporting
confidence: 64%
“…In Eastern culture, failure to identify and explain spiritual pain by specialists, lack of attention to the conceptualization of this pain, lack of education on this pain in the curricula of medicine, psychology, and even religious studies are the most important reasons for not paying attention to relieving this pain (Fasihizadeh & Nasiriani, 2020 ; Musa, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the duration of insertion most of them between 1 and 2 days (53.3%). Table (6) shows that high percentage of severe pain and anxiety for studied patients (88.3%, 98.3%) respectively before chest tube removal.…”
Section: Field Workmentioning
confidence: 93%